Emergency Department Management of the Covid-19 Pandemic - Schreyer, Kraftin E. (J Emerg Med, 2020)
BACKGROUND: Emergency departments (EDs) need to be prepared to manage crises and disasters in both the short term and the long term. The coronavirus disease 2019 (COVID-19) pandemic has necessitated a rapid overhaul of several aspects of ED operations in preparation for a sustained response. OBJECTIVE: We present the management of the COVID-19 crisis in 3 EDs (1 large academic site and 2 community sites) within the same health care system. DISCUSSION: Aspects of ED throughput, including patient screening, patient room placement, and disposition are reviewed, along with departmental communication procedures and staffing models. Visitor policies are also discussed. Special considerations are given to airway management and the care of psychiatric patients. Brief guidance around the use of personal protective equipment is also included. CONCLUSIONS: A crisis like the COVID-19 pandemic requires careful planning to facilitate urgent restructuring of many aspects of an ED. By sharing our departments’ responses to the COVID-19 pandemic, we hope other departments can better prepare for this crisis and the next.